STOP GLOBAL WARMING! AN ANDROID MOBILE GAME TO RAISE AWARENESS OF GLOBAL WARMING - Voon, Ming Chang (Universiti Malaysia Sarawak (UNIMAS), 2019)
The global warming issue has been persisting for a very long time. However, people still lack awareness of the severity of global warming. People tend to focus more on their work rather than taking care of their surroundings. Thus, the proposed game is developed to raise awareness of this global warming issue among people nowadays to prevent Global warming from getting worse. The methodology chose to create the proposed game is the agile methodology, which is error-tolerant and supports a fast development process. The overall design of the proposed game is determined after reviewing three existing mobile games present in the Google Play Store. Besides that, requirement analysis is also performed to find out the needs of the proposed game’s development. The requirement analysis process includes the distribution of the questionnaire (Appendix A) about people’s knowledge of Global warming and educational game. Furthermore, hardware, software and system requirements also analyzed to ensure the smoothness of the game development process.